2021
DOI: 10.3390/agriculture11121231
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Effect of Vermicompost on Yield and Physiological Indices of Container-Grown Dracocephalum moldavica Plants

Abstract: The development of sustainable plant production systems involves a search for different alternatives to chemical fertilizers. The aim of the present study is to compare growth and physiological effects of vermicompost on Dracocephalum moldavica plants in controlled conditions, using two types of commercially available substrates. The intention is to determine whether nondestructively measured photosynthesis-related parameters are useful for monitoring the physiological status of plants. The plants were cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In turn, it reduces the contents and activities of photosynthetic carbon reduction cycle enzymes, including the key enzyme, ribulose-1, 5-bisphosphate carboxylase-oxygenase. The study's present results agree with those obtained by Ose et al (2021), who found that vermicompost increased photosynthetic pigments synthesis and CO 2 assimilation rates due to reduced stomatal conductance. In addition, vermicompost contains available elements causing a reduction in the activities of photosynthetic carbon reduction cycle enzymes, including the key enzyme, ribulose-1, 5-bisphosphate carboxylase-oxygenase (Ievinsh, 2020).…”
Section: Photochemical Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…In turn, it reduces the contents and activities of photosynthetic carbon reduction cycle enzymes, including the key enzyme, ribulose-1, 5-bisphosphate carboxylase-oxygenase. The study's present results agree with those obtained by Ose et al (2021), who found that vermicompost increased photosynthetic pigments synthesis and CO 2 assimilation rates due to reduced stomatal conductance. In addition, vermicompost contains available elements causing a reduction in the activities of photosynthetic carbon reduction cycle enzymes, including the key enzyme, ribulose-1, 5-bisphosphate carboxylase-oxygenase (Ievinsh, 2020).…”
Section: Photochemical Activitysupporting
confidence: 92%
“…Vermicompost-tea application maximized active photosynthetic leaves and leaf area, maintaining the chlorophyll in higher concentrations. In this respect, Ose et al (2021) reported that chlorophyll concentration was positively affected by the vermicompost amendment in a concentration-dependent manner, however, this effect during a cultivation period appeared relatively late. (Hawkins and Lewis, 1993).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 97%
“…While all chlorophyll fluorescence-derived parameters obtained through fast induction kinetics are interlinked, each of them shows effects at specific points in the electron transport chain [ 30 ]. F v /F 0 is mostly affected by photochemical reactions at the donor side of photosystem II, including water-splitting activity [ 30 ], and changes in this parameter have been shown to be an important determinant of biomass accumulation of Dracocephalum moldavica plants at various fertilization regimes [ 32 ]. However, F v /F 0 did not show a direct relationship with growth at different mineral regimes in S. esthonica ( Figure 8 E) or biomass accumulation in plants at different soil moisture regimes ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VC aids in the greater completion of root formation in plants, resulting in plants that take nutrients from the soil more readily and perform better in terms of growth [21] . Due to the presence of humic acid, which is a chemical similar to plant growth hormone, VC treatments have been proven in several studies to be able to improve plant growth parameters such as height, fruit yield, stem width, water content, flower width, leaf length, leaf number, and leaf area [22–30] . Balmori et al.…”
Section: Resultsmentioning
confidence: 99%
“…[21] Due to the presence of humic acid, which is a chemical similar to plant growth hormone, VC treatments have been proven in several studies to be able to improve plant growth parameters such as height, fruit yield, stem width, water content, flower width, leaf length, leaf number, and leaf area. [22][23][24][25][26][27][28][29][30] Balmori et al explained that the foliar application of humic extract from VC at a 1 : 40 (v:v) on Allium sativum was the best treatment for growth parameters. They found that the humic substance increased the fruit quality and improved the bulb diameter.…”
Section: Resultsmentioning
confidence: 99%